T.-T. Marsalcovschi. Manuscripts by Dimitrie Balica, commissioner (Confluenţe Bibliologice, 2013)
At the book launch „Manuscripts” by Dimitrie Balica comisul, Beatrice Surugiu held a speech pointed out that today the manuscripts printing is very important. This is a proof that, during the period of denationalization of the country, it was written in the Romanian language. Thus compensated the existing literary deﬁcit in that period.
Keywords: book launch